2013
DOI: 10.1002/jobm.201200776
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of heavy metal inhibition of 1,2‐dichloroethane biodegradation in co‐contaminated water

Abstract: Sites co-contaminated with heavy metals and 1,2-DCA may pose a greater challenge for bioremediation, as the heavy metals could inhibit the activities of microbes involved in biodegradation. Therefore, this study was undertaken to quantitatively assess the effects of heavy metals (arsenic, cadmium, mercury, and lead) on 1,2-DCA biodegradation in co-contaminated water. The minimum inhibitory concentrations (MICs) and concentrations of the heavy metals that caused half-life doubling (HLDs) of 1,2-DCA as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The inhibitive concentration of Cd 2+ on trichloroaniline degradation could be as low as 0.01 mg/L in a mineral-dominated soil (Pardue et al, 1996). Previous studies suggested that Cd 2+ had inhibitory effects on 1,2-DCA degradation and the presence of 33.7 mg/L Cd 2+ resulted in partial 1,2-DCA degradation (Arjoon et al, 2015). Recently, another study also demonstrated that Cd 2+ was one of the most toxic heavy metal ions that inhibited the PCE-to-ethene dechlorination process in pure cultures, mixed cultures, and microcosms (Lu et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…The inhibitive concentration of Cd 2+ on trichloroaniline degradation could be as low as 0.01 mg/L in a mineral-dominated soil (Pardue et al, 1996). Previous studies suggested that Cd 2+ had inhibitory effects on 1,2-DCA degradation and the presence of 33.7 mg/L Cd 2+ resulted in partial 1,2-DCA degradation (Arjoon et al, 2015). Recently, another study also demonstrated that Cd 2+ was one of the most toxic heavy metal ions that inhibited the PCE-to-ethene dechlorination process in pure cultures, mixed cultures, and microcosms (Lu et al, 2020).…”
Section: Discussionmentioning
confidence: 92%